SHORT MULTIFREQUENCY VIBRATOR ANTENNA. II. ENGINEERING CALCULATION OF SHORT THICK VIBRATORS - Bovkoon, V. P.; Bubnov, I. N.; Gridin, A. A.; Zhouck, I. N. (Видавничий дім «Академперіодика», 2013)
The electrostatic method of engineering calculation of short thickvibrators is presented. This method allows to determinatethe parameters of vibrators with arm length of less than onetenth of operating wavelength providing the vibrator’s arm lengthto-radius ratio within 2 to 20. The equivalent circuit of suchvibrators is represented in the form of a three-element reactivetwo-terminal circuit with losses. The equivalent length generatingthe vibrator arm is introduced to account for the vibratorthickness in calculation of reactive resistance components of aseries circuit, whereas the effective length generating the equivalentvibrator arm is used to account for the vibrator thicknessin calculation of a series circuit inductance. The experimentallytested ten models confirm the results obtained with the proposedmethod.